New Treatment for Alzheimer's Disease, Kamikihito, Reverses Amyloid-β-Induced Progression of Tau Phosphorylation and Axonal Atrophy. (23rd February 2014) - Watari, Hidetoshi; Shimada, Yutaka; Tohda, Chihiro
Abstract : Aims. We previously reported that kamikihito (KKT), a traditional Japanese medicine, improved memory impairment and reversed the degeneration of axons in the 5XFAD mouse model of Alzheimer's disease (AD). However, the mechanism underlying the effects of KKT remained unknown. The aim of the present study was to investigate the mechanism by which KKT reverses the progression of axonal degeneration. Methods. Primary cultured cortical neurons were treated with amyloid beta (A β ) fragment comprising amino acid residues (25–35) (10 μ M) in an in vitro AD model. KKT (10 μ g/mL) was administered to the cells before or after A β treatment. The effects of KKT on A β -induced tau phosphorylation, axonal atrophy, and protein phosphatase 2A (PP2A) activity were investigated. We also performed an in vivo assay in which KKT (500 mg/kg/day) was administered to 5XFAD mice once a day for 15 days. Cerebral cortex homogenates were used to measure PP2A activity. Results. KKT improved A β -induced tau phosphorylation and axonal atrophy after they had already progressed. In addition, KKT increased PP2A activity in vitro and in vivo . Conclusions. KKT reversed the progression of A β -induced axonal degeneration. KKT reversed axonal degeneration at least in part through its role as an exogenous PP2A stimulator.